2004
DOI: 10.1177/107602960401000411
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Pathway Inhibitor and Thrombin Activatable Fibrinolytic Inhibitor Plasma Levels following Burnand Septic Injuries in Rats

Abstract: Burn and septic injuries induce profound changes in coagulation status. This study examined the changes in plasma tissue factor pathway inhibitor (TFPI) and thrombin activatable fibrinolytic inhibitor (TAFI) levels in a rat model of burn and septic injuries. Rats underwent 30% TBSA cutaneous scald burn injury and septic insult was induced by caecal ligation and puncture (CLP). CLP was superimposed on burn injury to mimic the clinical model of sepsis complicating burn injury. Rats were pretreated with Cprofloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
3
10
0
1
Order By: Relevance
“…Hepatic TAFI mRNA expression rapidly increased after endotoxin administration to rodents (19,20) and TAFI plasma levels were elevated during peritonitis induced by cecal ligation and puncture in rats (41). In line with these previous studies, we found that TAFI mRNA was expressed in the liver and became up-regulated during E. coli-induced peritonitis, which was accompanied by elevated TAFI protein levels in liver and plasma.…”
Section: Discussionsupporting
confidence: 78%
“…Hepatic TAFI mRNA expression rapidly increased after endotoxin administration to rodents (19,20) and TAFI plasma levels were elevated during peritonitis induced by cecal ligation and puncture in rats (41). In line with these previous studies, we found that TAFI mRNA was expressed in the liver and became up-regulated during E. coli-induced peritonitis, which was accompanied by elevated TAFI protein levels in liver and plasma.…”
Section: Discussionsupporting
confidence: 78%
“…21 Ravindranath et al examined the changes in plasma tissue factor pathway inhibitor (TFPI) and thrombin activatable fibrinolytic inhibitor (TAFI) levels in a rat model of burn and septic injuries by treating mice with 30% total body surface area cutaneous scald burn injury and caecal ligation and puncture (CLP). 29 The levels of TFPI decreased significantly at 24 hours in burn, CLP, and burn þ CLP groups, followed by incomplete rebound recovery at 72 hours in all three groups. Conversely, TAFI levels increased significantly at 24-and 72-hour time points in all three groups, suggesting that burn, sepsis, and their combined injuries might substantially perturb the coagulation cascade toward a procoagulant condition.…”
Section: Pathophysiology and Biochemistry Of Disseminated Intravasculmentioning
confidence: 87%
“…In a septic rat model with Pseudomonas aeruginosa, the inhibition of TAFIa reduced the systemic inflammatory response, thus suggesting that TAFI plays an important role in the deterioration of organ dysfunction in sepsis [10]. In a rat model of a sepsis-complicating burn injury, TAFI was elevated after 24 and 72 h, confirming the close link between inflammation and coagulation [11]. Septic patients, as well as healthy study subjects with low-grade lipopolysaccharide (LPS)-induced endotoxemia, showed decreased levels of TAFI [12,13], and in polytraumatized patients, TAFI levels inversely correlated with the inflammation-associated development of complications [14].…”
Section: Introductionmentioning
confidence: 84%